Monitoring the effects of vegetation cover losses on land surface temperature dynamics using geospatial approach in Rajshahi City, Bangladesh - Zullyadini A. Rahaman (Tanjung Malim, 2021)
Monitoring the effects of vegetation cover losses on land surface temperature dynamics using geospatial approach in Rajshahi City, Bangladesh by Zullyadini A. Rahaman